(untitled) (Research Announcements "Heritage BG", 2025)
An icon from the region of Shumen was provided for analysis of the colour palette, the gilding and the varnish coating (supposed to be dammar or mastic) at the Centre for Archaeometry with a Laboratory for Conservation and Restoration (CALCR), University of Sofia. For this purpose selected segments on the surface were studied by non-destructive methods with instruments like: portable X-ray spectrometer Titan S1 Bruker, micro-x-ray fluorescent spectrometer Mistral M1 Bruker, infrared spectrometer with a reflection and absorption variant Alfa II Bruker, Raman spectrometer Bravo1 Bruker. Refernces: Abdel-Ghani, M. (2015). Dating a Coptic Icon of Anonymus Painter by Spectroscopic Study of Pigment palette. – Mediterranean Archaeology and Archaeometry, Vol. 15, No 1, 23-37. Coccato, Alessia, Moens, Luc, Vandenabeele, Peter. (2017). On the Stability of Mediaeval Inorganic Pigments: a Literature Review of the Effect of Climate, Material Selection, Biological Activity, Analysis and Conservation Treatments. – Heritage Science, volume 5, 12. Konstantas, Alexander, Karapanagiotis, Ioannis, Boyatzis, Stamatis C. (2021). Identification of Colourants and Varnishes in a 14th Century Decorated Wood-Carved Door of the Dionysiou Monastery in Mount Athos. – Coatings 2021, 11, 1087, 1-12. Mafredas, Thomas. (2017). The Colour Palette in the Byzantine Icons. (LAB COURSE A4). Kalamata. Достъпно на: https://www.academia.edu/31740791/ (accessed: 01.06.22). Medhat, Abdallah, Ali, Mona, Abdel-Ghani, Mona. (2015). Analytical Investigation on a Coptic Wooden Icon from the 18th Century Using SEM-EDX Microscopy and FTIR Spectroscopy. – Mediterranean Archaeology and Archaeometry, 15, 1, 151-161. Mekaj, Eglantina, Civici, Nikolla. (2019). Investigation of the Pigments Used in two 16th Century Icons Attributed to Onufri: Non-destructive Analysis by a Portable XRF Spectrometer. – Buletini i shkencave natyrore (University of Tirana) 28, 218-231. Prati, Silvia, Volpi, Francesca, Fontana, Raffaella, Galletti, Paola, Giorgini, Loris, Mazzeo, Rocco, Mazzocchetti, Laura, Samorì, Chiara, Sciutto, Giorgia, Tagliavini, Emilio. (2018). Sustainability in Art Conservation: A Novel Bio-based Organogel for the Cleaning of Water Sensitive Works of Art. – Pure and Applied Chemistry, 90(2), 239-251. Sandu, Irina, de Sa, Helena, Pereira, Manuel. (2011). Ancient ‘Gilded’ Art Objects from European Cultural Heritage: A Review on Different Scales of Characterization.– Surface and Interface Analysis. Tauson, Vladimir R, Goettlinger, Joerg, Sapoznikov, Anatoly N., Mangold, Stefan, Lustenberg, Esfir E. (2012). Sulphur Speciation in Lazurite-type Minerals (Na,Ca) 8Al 6Si 6O 24 2 and TheirAnnealing Products: A Comparative XPS and XAS Study. – European Journal of Mineralogy, 24/1, 133-152.